Glossopharyngeal Neuralgia Treated with an Endoscopic Assisted Midline Suboccipital Subtonsillar Approach: Technical Note - Roser, Florian; Ebner, Florian Heinrich; Schuhmann, Martin U.; Tatagiba, Marcos (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Glossopharyngeal nerve neuralgia (GPN) is an exceptionally rare skull-based disorder. It is treated similar to other neurovascular conflicts. The approach, however, is debatable, as the caudal cranial nerves and especially the exit zones at the brainstem are barely visible via the retrosigmoid approach.Clinical Presentation We demonstrate a case of a typical GPN with microsurgical neurovascular decompression according to standard procedures. Continuous electrophysiological monitoring, including motor-evoked potentials of the glossopharyngeal nerve in addition to somatosensory evoked potential (SSEP) monitoring, was set up. In prone position a midline suboccipital osteoplastic craniotomy was performed. Intradurally, an endoscopic-assisted subtonsillar exposure of the lateral recess and the nerve root exit zone of the glossopharyngeal nerve has been chosen. A large compressing branch of the posterior inferior cerebellar artery (PICA) was identified as the cause of the neurovascular conflict and transposed.Conclusions A midline subtonsillar approach with endoscopic assistance to the lateral brainstem is a straightforward time- and morbidity-sparing procedure.
Keywords: endoscopy-assisted microsurgery; endoscopy-skull base; minimally invasive endoscopy; skull base